The IoT Simulation of Watering System for Vanilla Cultivation using DHT11 and Soil Moisture Sensors with Fuzzy Logic Control - Akhlak, Muhammad Lutfi Mahasinul; Azizah, Isnaini Nurul; Nataliya, Desi; Maghfiroh, Fatiya; Febriani, Yeza (Universitas Muhammadiyah Magelang, 2025)
The primary objective of this study is to design and simulate an automatic watering system utilizing a DHT11 sensor and a soil moisture sensor for vanilla cultivation, incorporating fuzzy logic control. The system can effectively adjust watering frequency based on soil moisture and ambient temperature, ensuring optimal plant care and maintaining ideal growth conditions for vanilla without manual intervention. Using the ADDIE development model, this system was designed to meet the needs of users, including farmers. Testing using MATLAB software using Rule Viewer and Simulink, as well as Arduino IDE software running with Proteus, yielded the same output values when the input values were also identical. Therefore, the IoT simulation of vanilla cultivation using fuzzy logic control can be effectively implemented in accordance with the research objectives. The results of this study demonstrate the great potential of applying IoT technology to support efficiency and effectiveness in plant maintenance. This system also provides an efficient and accurate monitoring solution compared to manual methods, operating automatically without requiring human intervention.